Optimalisasi E-Learning Berbasis Virtual Class dengan Google Classroom sebagai Media Pembelajaran Fisika - Erfin Nurfalah (Faculty of Science and Education, UIN Walisongo Semarang, 2019)
Lately, the era of industrial revolution 4.0 has become a global conversation. Now the world is witnessing technological developments in all sectors. So that these developments bring positive things even in the field of education. However, this is also a challenge for educators 4.0, where technological literacy skills must be possessed. 21st century competence requires that students be directly involved in the learning process that utilizes the internet, where students are not only limited to seeking information, but also carry out online learning. The purpose of this research is to describe e-learning based on virtual classes with google classroom as a medium for learning physics. The method used is a literature study. Basic features of google classroom consist of topics, teaching materials, questions, quiz assignments, and assignments. Optimizing the features of google classroom has an important impact on learning in the era of industrial revolution 4.0, including: (1) learning is done online by utilizing technology, (2) not limited by space and time, (3) students are directly involved in the learning process utilizing the internet, (4) learning material that is easy to access, (5) training data literacy skills and technology literacy. Google classroom is an internet-based service provided by Google with an e-learning system. So that it can be used as an efficient, effective and interactive learning media to support technology-based learning.